Radioiodination of Aryl-Alkyl Cyclic Sulfates - Mikhail I. Papisov; Chandra Mushti (Molecules, 2012)
Among the currently available positron emitters suitable for Positron Emission Tomography (PET), 124I has the longest physical half-life (4.2 days). The long half-life and well-investigated behavior of iodine in vivo makes 124I very attractive for pharmacological studies. In this communication, we describe a simple yet effective method for the synthesis of novel 124I labeled compounds intended for PET imaging of arylsulfatase activity in vivo. Arylsulfatases have important biological functions, and genetic deficiencies of such functions require pharmacological replacement, the efficacy of which must be properly and non-invasively evaluated. These enzymes, even though their natural substrates are mostly of aliphatic nature, hydrolyze phenolic sulfates to phenol and sulfuric acid. The availability of [124I]iodinated substrates is expected to provide a PET-based method for measuring their activity in vivo. The currently available methods of synthesis of iodinated arylsulfates usually require either introducing of a protected sulfate ester early in the synthesis or introduction of sulfate group at the end of synthesis in a separate step. The described method gives the desired product in one step from an aryl-alkyl cyclic sulfate. When treated with iodide, the source cyclic sulfate opens with substitution of iodide at the alkyl center and gives the desired arylsulfate monoester.